KOMUNIKASI TERAPEUTIK DOKTER DAN PASIEN PADA BAGIAN PENYAKIT DALAM DI RUMAH SAKIT UMUM ANUTAPURA PALU - Torile, Renaldo Martin Kristanto (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2018)
This study was conducted aimed at finding out the therapeutic communication (interpersonal) of doctors in approaching patients on examination activities. The research method used is qualitative research with descriptive methods. Location is located at Anutapura Palu General Hospital Jl. Kangkung No. 1. The number of informants in this study were 6 (six) people with accidental sampling withdrawal techniques by determining the criteria determined by the researcher. Data collection techniques are carried out by observation and interviews. The data analysis technique uses qualitative data analysis. The results showed that the doctor's therapeutic communication and internal medicine patients can be seen based on direct interpersonal communication, namely the first reaction, lack of reaction indicated by the doctor at the introductory stage or the beginning of the examination. good by giving the right advice for healing patients. Both relationships, doctors build good relationships by approaching patients and providing fair services to patients they handle. The third message flow, communication is established where the doctor as the leader and director in communication so that the patient gets a medical consultation and good understanding.